THE EFFECT OF SELF-REGULATED ORIENTED LEARNING ON STUDENTS ACHIEVEMENT AND PERCEPTIONS IN ENVIRONMENTAL POLLUTION MATERIAL - Fitriyaningsih, Sari; Susantini, Endang; Rahayu, Yuni Sri (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
To achieve the 2013 curriculum aims, which is, to prepare Indonesian people that have the ability to live as individuals and citizens who believe, productive, creative, innovative, effective and able to contribute to society, nation, and world civilization, teachers should educate students to become self-regulated learner. The previous studies found that self-regulated learning not only improves students learning, but it also improves their perceptions. Therefore, the aims of this research were to implemented a certain SRL's elements on pollution topic. It were also to evaluate the effect of self-regulated oriented learning on students achievement and students perception. This research involved 64 experienced students from 2 classes in 7th grade of Junior High School 1 Lamongan. This research was conducted in three phases, that are, the development of research instruments, validation of those instruments, and implementation of those instruments in the classroom. The findings showed that SRL implementation in terms of Lesson Plans and worksheet feasibility is in good categories. It was also affected on the students' perceptions of constructivist learning environments about 82.1%, affected on the students' acquired knowledge results about 72.5%, and affected on the students' process skill results about 76.8%. Due to the results, it can be concluded that implementation of SRL was effective for the learners